GAMBARAN KEJADIAN FILARIASIS BERDASARKAN KARAKTERISTIK PADA PENDONOR DARAH DI KOTA DAN KABUPATEN PEKALONGAN - Ikrimah Nafilata; Alpha Olivia Hidayati; Meyta Wulandari (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
The Descriptions of Filariasis Incidence Based On Characteristics Blood Donors in Pekalongan City and RegencyBackground : Pekalongan City and Regency are still endemic areas of Filariasis in Indonesia with Microfilaria Rate > 1%. Screening tests on donor blood at local blood donor units for filariasis have not been carried out, it is necessary to screen blood donors for safety of blood products and as an evaluation of Filariasis Mass Drug Administration Programs.  Objective : This Research are the descriptions of Filariasis Incidence based on Characteristics Blood Donors by screening using the ELISA method. Methods : This Research is an observational descriptive Cross Sectional design, with a total sample of 84 donors. Results : Filariasis positive results were obtained in Pekalongan City by 13 (31.0%) and in Pekalongan Regency by 15 (35.7%). Conclusion : Based on the results of screening using ELISA, there were still 28 positive filariasis from a total of 84 samples.